LEGAL PROTECTION TO THE PEDESTRIAN RIGHT - Kadek Erma Karlyana; Galih Puji Mulyono (Jurnal Pembaharuan Hukum, 2018)
Walking is one of the main modes of human transportation before the emergence of various other means of transportation that support the movement or movement of humans. In the midst of the rapid development of transportation, safety from pedestrians began to be overlooked by the increasing percentage of traffic accidents involving pedestrians as victims. The neglect of pedestrian protection is a form of violation of human rights that is the basic right of the pedestrian itself as the weakest mode of transportation. The neglect of the protection of pedestrian human rights is caused by several factors such as the availability of inadequate facilities such as the conversion of pedestrian lines by street vendors, the lack of awareness from the public regarding law enforcement on pedestrian protection to the lack of government role in it. The purpose of writing this topic is to raise public awareness about the importance of protection of pedestrian rights by not escape the existence of cooperation from the government so that the rights can be fulfilled as stated in the Act.